The costs and benefits of multicellular group formation in algae*. (20th March 2019) - Kapsetaki, Stefania E.; West, Stuart A.
Abstract: The first step in the evolution of complex multicellular organisms involves single cells forming a cooperative group. Consequently, to understand multicellularity, we need to understand the costs and benefits associated with multicellular group formation. We found that in the facultatively multicellular algae Chlorella sorokiniana : (1) the presence of the flagellate Ochromonas danica or the crustacean Daphnia magna leads to the formation of multicellular groups; (2) the formation of multicellular groups reduces predation by O. danica, but not by the larger predator D. magna ; (3) under conditions of relatively low light intensity, where competition for light is greater, multicellular groups grow slower than single cells; (4) in the absence of live predators, the proportion of cells in multicellular groups decreases at a rate that does not vary with light intensity. These results can explain why, in cases such as this algae species, multicellular group formation is facultative, in response to the presence of predators.